Analysis of User Satisfaction Level of the Dana Application in Dki Jakarta - Hasan Rifai (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze the level of user satisfaction with the DANA application in Jakarta. The research employs Purposive Sampling by selecting respondents based on the criteria of having transacted using the DANA application and being at least 17 years old. Data were collected through questionnaires distributed to respondents residing in Jakarta to obtain the necessary information according to the variables studied. The data obtained were analyzed using descriptive analysis techniques, mean tests, standard deviation tests, and t-tests. The results of this study indicate that users agree on the dimensions of user convenience, system information management, application usability, and intention to reuse. Based on the mean test, the user convenience dimension scored an average of 3.98, the system information management dimension scored an average of 3.95, the application usability dimension scored an average of 4.01, and the intention to reuse dimension scored an average of 4.04. This indicates that users agree that the DANA application can be used easily with a comfortable interface design, allowing users to find information in an organized manner and utilize all offered features, leading to user satisfaction and the intention to use the application for future transactions.